Polarization and Accountability in Covid Times - Beramendi, Pablo; Rodden, Jonathan (Frontiers in Political Science, 2022)
Career-minded incumbents might be willing to tolerate surprisingly high death rates in polarized democracies. When voters perceive the out-party to be ideologically extreme, they are less likely to hold incumbents accountable for death rates. Knowing this, incumbents face weaker incentives to take politically costly measures that would minimize deaths. In polarized democracies, there is a partisan asymmetry whereby the additional government intrusion associated with effective COVID response is more politically costly for the right than for the left, because it undercuts the ideological distinctiveness that drives the base-mobilization strategy of the right. This generates incentives for politicization of COVID mitigation policies that ultimately lead to partisan differences in mitigation behavior. Consistent with this logic, we provide preliminary evidence that COVID death rates are higher in more polarized democracies, and that in one of the most polarized democracies—the United States—COVID deaths have become increasingly concentrated over time in rural, Republican counties.